2003
DOI: 10.1080/10556790310001609106
|View full text |Cite
|
Sign up to set email alerts
|

OPTICALR-BAND PHOTOMETRY OF TeV BL Lac OBJECTS: 1ES1959 + 650 AND 1ES2344 + 514

Abstract: We present the results of R-band observations of two TeV BL Lacertae objects 1ES1959 þ 650 and 1ES2344 þ 514. To study the long-term variability (LTV) intraday variability (IDV) and intrahow variability (IHV) we observed these objects for 72 and 39 nights respectively. The LTV of 1ES1959 þ 650 has a magnitude of 0.4, while it is below 0.1 in the case of 1ES2344 þ 514. The IDV and IHV of both objects have magnitudes less than 0.01. The higher activity of 1ES1959 þ 650 in comparison with that of 1ES2344 þ 514 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Variability is one of the typical observational properties of blazars. As a TeV blazar, 1ES 2344 + 514 has been studied in the optical bands in the past 20 years (Miller et al 1999;Dai et al 2001;Kurtanidze & Nikolashvili 2002;Xie et al 2002;Kurtanidze et al 2003;Fan et al 2004;Kurtanidze et al 2004Kurtanidze et al , 2005Ma et al 2010;Gaur et al 2012;Pandey et al 2020). However, intraday variability has seldom been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability is one of the typical observational properties of blazars. As a TeV blazar, 1ES 2344 + 514 has been studied in the optical bands in the past 20 years (Miller et al 1999;Dai et al 2001;Kurtanidze & Nikolashvili 2002;Xie et al 2002;Kurtanidze et al 2003;Fan et al 2004;Kurtanidze et al 2004Kurtanidze et al , 2005Ma et al 2010;Gaur et al 2012;Pandey et al 2020). However, intraday variability has seldom been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, Dai et al (2001) reported their optical observations and found a 0.14 mag IDV in the V band within 26 minutes. In order to study long-term variations and IDVs, optical R-band observations of two TeV BL Lac sources 1ES 1959 + 650 and 1ES 2344 + 514 have been carried out with the 70 cm telescope in Abastumani Observatory, Georgia (Kurtanidze & Nikolashvili 2002;Kurtanidze et al 2003Kurtanidze et al , 2004Kurtanidze et al , 2005. These sources were observed for 72 nights and 39 nights, respectively.…”
Section: Introductionmentioning
confidence: 99%